2023
DOI: 10.3389/fpubh.2023.1189173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between body habitus and frailty of community adults in Chongqing: a cross-sectional survey study

Aini Chen,
Li Ren,
Su Min
et al.

Abstract: ObjectiveCurrently, a multitude of studies are underway to investigate the factors affecting the degree of frailty, with a significant focus on the critical role of body mass index (BMI). This study aims to conduct a cross-sectional survey to investigate the multifaceted relationship between multiple body habitus and the factors that influence the degree of frailty.MethodsA questionnaire survey was conducted among 840 adult residents in Chongqing communities. A total of 723 participants were included in the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…A substantial body of epidemiological research has examined the possible link between the regular omission of breakfast and increased frailty. For instance, a cross-sectional survey involving 723 adults from communities in Chongqing found that consistent breakfast consumption significantly reduces the likelihood of frailty [ 60 ]. Furthermore, a study with 3,758 individuals aged 60 and over indicated that daily breakfast intake might act as a protective factor, lessening the risk of developing prefrailty and frailty, the study also highlighted that the adverse long-term impacts of omitting breakfast on cognitive functions could be attributed to its association with heightened cardiometabolic risks [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of epidemiological research has examined the possible link between the regular omission of breakfast and increased frailty. For instance, a cross-sectional survey involving 723 adults from communities in Chongqing found that consistent breakfast consumption significantly reduces the likelihood of frailty [ 60 ]. Furthermore, a study with 3,758 individuals aged 60 and over indicated that daily breakfast intake might act as a protective factor, lessening the risk of developing prefrailty and frailty, the study also highlighted that the adverse long-term impacts of omitting breakfast on cognitive functions could be attributed to its association with heightened cardiometabolic risks [ 61 ].…”
Section: Discussionmentioning
confidence: 99%